2018
DOI: 10.5155/eurjchem.9.4.360-368.1774
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and crystal structure of platinum(II) complexes with thiourea derivative ligands

Abstract: Thiourea derivatives [N-(di-n-propylcarbamothioyl)-4-fluorobenzamide (HL1) and N-(di-n-propylcarbamothioyl)-4-bromobenzamide (HL2)] and their platinum complexes have been successfully synthesized and structurally characterized by spectroscopic 1H NMR, 13C NMR, COSY, HMQC, and FT-IR techniques. The structure of both complexes was also confirmed by single crystal X-ray diffraction studies. The study of X-ray single crystal diffraction shows that the supramolecular aggregation of the complexes is stabilized via w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…From a thermodynamic point of view, the photoexcited electrons in the CB of Bi 3.84 W 0.16 O 6.24 will migrate into the CB of Bi 2 WO 6 , which further transfer to the CB of CuO; hence, the electron−hole recombination was effectively suppressed. 37,38 This electron transfer was also confirmed from XPS analysis, wherein a positive binding energy shift was observed in the case of Bi 4f and W 4f in CuO/biphase-BW, which correlates to electron scarcity in biphase-BW. Photoexcited electrons in the CB of nanohybrids effectively reduce Cr(VI).…”
Section: Mechanistic Insight For Enhanced Photocatalyticmentioning
confidence: 60%
“…From a thermodynamic point of view, the photoexcited electrons in the CB of Bi 3.84 W 0.16 O 6.24 will migrate into the CB of Bi 2 WO 6 , which further transfer to the CB of CuO; hence, the electron−hole recombination was effectively suppressed. 37,38 This electron transfer was also confirmed from XPS analysis, wherein a positive binding energy shift was observed in the case of Bi 4f and W 4f in CuO/biphase-BW, which correlates to electron scarcity in biphase-BW. Photoexcited electrons in the CB of nanohybrids effectively reduce Cr(VI).…”
Section: Mechanistic Insight For Enhanced Photocatalyticmentioning
confidence: 60%
“…When the 1 H NMR data of the ruthenium complexes synthesized in the structure [RuCl(CO)(PPh 3 ) 2 L] are collectively evaluated, the signal of the N H proton (δ 8.26–8.19 ppm) that appeared in the 1 H NMR spectra of the ligands is not observed in the complex 1 H NMR spectrum. When the ligand formed a monoanionic bidentate with the Ru(II) center through oxygen and sulfur atoms, it seems that amidic protons (C(O)‐NH‐C(S) moiety) underwent deprotonation 37–40 . The aromatic proton for the ligands appears at δ 7.43–7.83 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…1C). 30 Recently, Frei et al have reported antibacterial activity of [PtCl 2 (COD)] and its derivatives against S. aureus and observed a significantly higher activity when halogens are maintained as co-ligands (Fig. 1D).…”
Section: Introductionmentioning
confidence: 91%
“…31 Several groups have investigated Pt-nanoparticle-and Pt(II)-complex-based antimicrobials. 30,[32][33][34] These examples reveal the potential of Pt-based compounds for use as antimicrobial agents where access to the metal ions is controlled by the choice of ligands.…”
Section: Introductionmentioning
confidence: 99%